2002
DOI: 10.1046/j.1365-2133.2002.04916.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of sarco/endo-plasmic reticulum Ca2+-ATPase type 2 isoforms (SERCA2) in normal human skin and mucosa, and Darier's disease skin

Abstract: These findings support the hypothesis that SERCA2 is an important player in cutaneous biology, and provide baseline data that will facilitate the design and interpretation of functional studies of cutaneous SERCA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…The recent demonstration that DD may be caused by a mutation which affects only the 2b isoform of SERCA2 is consistent with a major role for this isoform in epidermis 16 . We did not see the consistently increased SERCA2 staining of basal epidermal cells which has been reported previously 6 …”
Section: Discussionsupporting
confidence: 86%
“…The recent demonstration that DD may be caused by a mutation which affects only the 2b isoform of SERCA2 is consistent with a major role for this isoform in epidermis 16 . We did not see the consistently increased SERCA2 staining of basal epidermal cells which has been reported previously 6 …”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we have confirmed that SERCA2 antibody showed cytoplasmic staining of normal epidermal cells, eccrine secretory ducts, sebaceous glands and hair follicles as previously reported [2]. Furthermore, a statistically significant decrease in the expression of SERCA2 was also found in DD involved epidermis as compared to uninvolved DD epidermis using the antibodies specific to C-terminal peptides of SERCA2.…”
supporting
confidence: 95%
“…SERCA2 is highly expressed in keratinocytes and has been localized to ER [1]. Mutations in ATP2A2 probably cause a partial deficiency of the SERCA2 pump [2]. HHD arises from mutational inactivation of one allele of ATP2C1 [3,4], which encodes the human secretory pathway Ca 2+ /Mn 2+ ATPase1 (hSPCA1).…”
mentioning
confidence: 99%
“…A changes in Ca 2+ signaling and Ca 2+ ‐dependent cellular functions in SERCA2 +/− mice has been reported in a variety of tissues (17,27,28) . In this study, we first examined whether altered Ca 2+ signaling by partial deletion of SERCA2 alters osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…A changes in Ca 2+ signaling and Ca 2+ -dependent cellular functions in SERCA2 +/mice has been reported in a variety of tissues. (17,27,28) In this study, we first examined whether altered Ca 2+ signaling by partial deletion of SERCA2 alters osteoclastogenesis. To determine the specific role of SERCA2 in osteoclastogenesis, WT and SERCA2 +/tibias were dissected, and BMD was measured by histological and microradiographical analyses.…”
Section: Severe Osteopetrosis In Serca2 +/Micementioning
confidence: 99%